Assassin bugs (Hemiptera: Heteroptera: Reduviidae) of Uruguay: A synoptic catalogue as a contribution to the study of Austral biodiversity - Martin Park, Abdiel Agustin (2011)
The first synoptic catalogue of Reduviidae is given to Uruguay including nine subfamilies, Ectrichodiinae (4), Emesinae (1), Hammacerinae (1), Harpactorinae (11), Peiratinae (4), Phymatinae (3), Reduviinae (5), Stenopodainae (7), Triatominae (9), being Harpactorinae and Triatominae the best represented by eleven and nine species respectively. Criceptopareis tucumana (Berg) is mentioned for the first time for Uruguay and is confirmed the distribution for Atrachelus cinereus (Fabricius), Melanolestes argentinus Berg, Rasahus hamatus (Fabricius), Zelurus femoralis femoralis (Stål), Diaditus semicolon Stål, Triatoma infestans (Klug) and Triatoma rubrovaria (Blanchard) from the material belonging to the Museo de La Plata (Argentina). This information is of valuable for insect’s conservation biodiversity programs.